2016
DOI: 10.1039/c5tb02027a
|View full text |Cite
|
Sign up to set email alerts
|

Surface micropatterning with zirconia and calcium phosphate ceramics by micromoulding in capillaries

Abstract: Micropatterning of silicon surface with bioinert yttria-stabilised zirconia or bioactive calcium phosphate ceramic by micromoulding in capillaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…To assess cell shape on different substrates by SEM and fluorescence microscopy, the cells were cultured for 24 hours in BM. This time point, at which a sufficient number of cells was attached on the surface to allow analysis, but the cells were not confluent yet, was selected based on the previous work, which showed that the effect of surface microfeatures on cell shape occurred early, and the maintenance of this effect was dependent on the properties of the substrate [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…To assess cell shape on different substrates by SEM and fluorescence microscopy, the cells were cultured for 24 hours in BM. This time point, at which a sufficient number of cells was attached on the surface to allow analysis, but the cells were not confluent yet, was selected based on the previous work, which showed that the effect of surface microfeatures on cell shape occurred early, and the maintenance of this effect was dependent on the properties of the substrate [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Right: SEM micrograph of MG63 cells cultured on patterned ceramic for 72 h. Scale bar: 20 µm (Adapted with permission. [131] Copyright 2016, Royal Society of Chemistry) microstructure or micron-scale biomaterial particles with defined geometry. The additive manufacturing of biomaterials using microfluidic print heads [111][112][113] is an important example of the use of microfluidics in biomaterials fabrication with a resolution that is often higher than that of other additive manu-facturing techniques.…”
Section: Production Of Microstructured and Microscale Biomaterials With Defined Shape On Chipmentioning
confidence: 99%
“…3) A schematic representation of the process of surface micropatterning with CaP ceramics by micromoulding in capillaries, including a) casting of polydimethylxyloxane (PDMS) and curing to develop a mould, b) air plasma treatment, c) infiltration of a CaP solution into the channels, d) drying and e) mold removal. Adapted with permission . 2015, the Royal Society of Chemistry.…”
Section: Role Of Physical Propertiesmentioning
confidence: 99%
“…Structural patterning has already been widely used for polymeric biomaterials, since polymers are more amenable to various patterning techniques as compared to brittle and hard ceramic materials. Nevertheless, several techniques, such as micromachining or laser ablation, have been used to obtain patterned surfaces in (bioinert) ceramics, although their accuracy is below 100 µm . The use of microfabrication technologies, such as soft lithography, allows for ceramic patterning with higher accuracy.…”
Section: Role Of Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation